Preparation of porous TiN coating on 310 stainless steel by the PIRAC titanisation-nitriding process. (3rd July 2022) - Chen, Yue; Wu, Shoujun; He, Wei; Zhang, Bin; Yang, Wenyu; Fu, Guo
ABSTRACT: Porous titanium nitride coatings are prepared on 310 stainless steel by the powder immersion reaction-assisted coating (PIRAC) titanisation-nitriding process. For titanisation below 950°C for 30 min, the detected phases on 310 steel are FeTi, Fe2 Ti and TiN. Titanisation at 1000°C for 30 min, the detected phases on 310 steel are FeTi, Fe2 Ti, TiN and Ti. After further nitriding at 800°C for 8 h, titanium nitride coating composed of TiN, Ti2 N and TiN0.3 can be formed. Pore size and porosity of the prepared coating are decreased with increasing titanisation temperature, while the uniformity of the pores in the coating and hardness of the coating is increased with increasing titanisation temperature. Microhardness of the porous PIRAC TiN coating prepared by titanisation at 900°C + nitriding at 800 °C, titanisation at 950°C + nitriding at 800 °C and titanisation at 1000°C + nitriding at 800°C is 8.65, 8.98 and 9.66 GPa, respectively.